Writing politics in Imperial Rome - Dominik, William J.; Garthwaite, J.; Roche, P. A. (Brill's Companions to Classical Studies., 2009)
Roman literature is inherently political in the varied contexts of its production and the abiding concerns of its subject matter. This collection examines the strategies and techniques of political writing at Rome in a broad range of literature spanning almost two centuries, differing political systems, climates, and contexts. It applies a definition of politics that is more in keeping with modern critical approaches than has often been the case in studies of the political literature of classical antiquity. By applying a wide variety of critically informed viewpoints, this volume offers the reader not only a long view of the abiding techniques, strategies, and concerns of political expression at Rome but also many new perspectives on individual authors of the early empire and their republican precursors.